THE EFFECTIVENESS OF THE HOPE FAMILY PROGRAM (PKH) IN SUPPORTING THE EDUCATION OF UNAFFICIENT STUDENTS IN THE PULAU RENGAS VILLAGE, PANGEAN DISTRICT, KUANTAN SINGI DISTRICT, 2018 - Agus Priyanto; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Family of Hope Program (PKH) is a social protection program that provides assistance to beneficiary families (KPM) and members of the beneficiary family are required to carry out predetermined terms and conditions. PKH aims to build a social protection system in order to break the chain of poverty, improve the quality of human resources, and improve the welfare of poor families.This study aims to determine the effectiveness of the Family Hope Program (PKH) in Supporting the Education of Underprivileged Students in Pulang Rengas Village, Pangean District, Kuantan Singingi Regency in 2018. This research uses descriptive qualitative methods with data collection techniques through interviews and documentation.Based on the results of the study showed that the Family Hope Program (PKH) in Pulau Rengas Village was not yet prosperous for poor families. However, the Family Hope Program (PKH) has helped Poor Households (RTM) reduce the burden on poor households in fulfilling education. The Family Hope Program (PKH) in Pulau Rengas Village is still not on target. This happens because at the time the PKH beneficiary candidates were proposed, they were still classified as poor, the time span for receiving assistance was relatively long so that the community had experienced developments on the economic side. Then the impact caused by the Effectiveness of the Family Hope Program (PKH) in Supporting the Education of Underprivileged Students in Pulau Rengas Village, Pangean District, Kuantan Singingi Regency is divided into two, namely, Positive Impact, namely 1). Can help poor families who are PKH participants to pay for their children to go to school. 2). Increase participation of school children. 3). Increase children's motivation to learn and the negative impacts, namely 1). People always depend on help. 2). Lack of PKH participant participation. 3). Social jealousy. Keywords: Effectiveness, Hope Family Program, Education, Impact.